2001
DOI: 10.1128/jvi.75.3.1561-1564.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of bcl-2 in Epstein-Barr Virus-Induced Malignant Conversion of Burkitt's Lymphoma Cell Line Akata

Abstract: We have demonstrated that Epstein-Barr virus (EBV) confers enhanced growth capability in soft agarose, tumorigenesis in the SCID mouse, and resistance to apoptosis in the Burkitt's lymphoma cell line Akata. Subsequently, we have shown that EBV-encoded small RNAs (EBERs) are responsible for these phenotypes. We constantly observed the upregulation of bcl-2 oncoprotein expression upon EBV infection and expression of EBERs. To test whether these phenotypes were due to the upregulation of bcl-2 expression, we intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 26 publications
6
115
0
Order By: Relevance
“…Their expression is nuclear and although its function is unknown it is strongly believed that they have an oncogenic role. 29 Our PCR-based analysis has shown to be concordant with the EBER results. The semiquantitative results also differentiate between passenger and productive viral presence as absorbance values indicate DNA-relative quantity.…”
Section: Discussionsupporting
confidence: 78%
“…Their expression is nuclear and although its function is unknown it is strongly believed that they have an oncogenic role. 29 Our PCR-based analysis has shown to be concordant with the EBER results. The semiquantitative results also differentiate between passenger and productive viral presence as absorbance values indicate DNA-relative quantity.…”
Section: Discussionsupporting
confidence: 78%
“…Various studies have shown that EBV inhibition of apoptosis and up-regulation of the Bcl-2 protein are essential for the malignant phenotype (Marin et al, 1995;Komano et al, 1998). Previous reports also provided direct evidence that EBV up-regulates Bcl-2 expression by repressing the activation of the double-stranded RNA-dependent protein kinase (PKR) (Komano et al, 1999). This allows c-MYC to exert its oncogenic function, and eventually results in the inhibition of apoptosis.…”
Section: Eber-1 and Eber-2 Up-regulate Bcl-2 Protein Expressionmentioning
confidence: 90%
“…First, EBERs affect membrane signaling by initiating the production of various interleukins (ILs) that are involved in cell growth, such as IL-6, IL-9, or insulin-like growth factor-1 (Ho et al, 1999;Kitagawa et al, 2000;Iwakiri et al, 2003;Iwakiri et al, 2005). They also play a role in regulation of apoptosis by binding the RNA-dependent protein kinase (PKR), subsequently inhibiting PKRmediated apoptosis in the EBV infected cells (Komano et al, 1999;Yamamoto et al, 2000). In addition, EBERs can modulate interferon (IFN)/antiviral response.…”
Section: Treatment Strategies For the Patients With Ebv-associated Chlmentioning
confidence: 99%
“…Nt (Ho et al, 1999;Komano et al, 1999;Kitagawa et al, 2000;Yamamoto et al., 2000;Iwakiri et al, 2003;Iwakiri et al, 2005;Samanta et al, 2006;Samanta et al, 2008;Iwakiri et al, 2009;Iwakiri and Takada, 2010 Immunization with LMP1 gene or polyepitope expression vectors Taylor et al, 2004;Smith et al, 2006;Pan et al, 2009;Lutzky et al, 2010;Chia et al, Immunization with LMP2A gene or polyepitope expression vectors (Taylor et al, 2004;Smith et al, 2006;Pan et al, 2009;Lutzky et al, 2010;Chia et al, 2011) LMP2B Modulation of innate immune response nt TLR: Toll-like receptor, RIG: retinoic acid-inducible gene, PKR: RNA-dependent protein kinase, Nt: not tested, CTL: cytotoxic T lymphocyte, DC: dendritic cells.…”
Section: Inhibition Of Apoptosis (Pkr)mentioning
confidence: 99%